2018
DOI: 10.1002/acn3.544
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐computer interfaces for post‐stroke motor rehabilitation: a meta‐analysis

Abstract: Brain‐computer interfaces (BCIs) can provide sensory feedback of ongoing brain oscillations, enabling stroke survivors to modulate their sensorimotor rhythms purposefully. A number of recent clinical studies indicate that repeated use of such BCIs might trigger neurological recovery and hence improvement in motor function. Here, we provide a first meta‐analysis evaluating the clinical effectiveness of BCI‐based post‐stroke motor rehabilitation. Trials were identified using MEDLINE, CENTRAL, PEDro and by inspec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
307
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 365 publications
(326 citation statements)
references
References 69 publications
15
307
0
4
Order By: Relevance
“…It is not clear, however, to what extent stroke patients in particular benefit from an EFS, since most paradigms have been tested only with healthy individuals. A recent meta-analysis conducted by Cervera et al (2018) showed that brain-computer interface (BCI)-based neurorehabilitation on upper-limb motor function can lead to more improvement in motor performance than other conventional therapies, supporting the general effectiveness of classical NF-MIT in stroke patients. The specific effect of EFS, however, has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear, however, to what extent stroke patients in particular benefit from an EFS, since most paradigms have been tested only with healthy individuals. A recent meta-analysis conducted by Cervera et al (2018) showed that brain-computer interface (BCI)-based neurorehabilitation on upper-limb motor function can lead to more improvement in motor performance than other conventional therapies, supporting the general effectiveness of classical NF-MIT in stroke patients. The specific effect of EFS, however, has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent studies have revealed the potential of NF and BCI training for stroke rehabilitation (Cervera et al, 2018), as an alternative or in addition to traditional therapies (Wang et al, 2017), to stimulate neural plasticity and support functional improvement (Grosse-Wentrup et al, 2011). Previous works have also shown that NF can enhance the efficacy of motor imagery training, in terms of eliciting brain patterns relevant to the task (Zich et al, 2015;Bagarinao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The NIRS-based MI-BCI, even during a short period (six sessions), seemed to benefit acute stroke patients compared with sham intervention (Mihara et al, 2013). (Cervera et al, 2018). Besides those mentioned, several other studies with similar purposes have been conducted in stroke patients (Buch et al, 2008;Caria et al, 2011;Prasad, Herman, Coyle, McDonough, & Crosbie, 2010;Varkuti et al, 2013) and depicted some interesting findings.…”
Section: Effects Of Bci Training In Upper Limb Functionmentioning
confidence: 85%
“…The authors interpreted these findings by suggesting that BCI training strengthens neuroplasticity, leading to a better recovery, because MI through BCI involves the same neural mechanisms that control voluntary movement of the hand . Several neuroplasticity changes due to BCI such as increasing premotor area activity or enhancement of ipsilesional connectivity with changes in hemispheric EEG activity were mentioned (see Cervera et al, 2018). However, care must be considered Additionally, more updated literature stated that when relating the combination of real tDCS Kasashima-Shindo et al, 2015) or sham with 1-hr EEG-based MI-BCI to a robotic feedback, both groups improved functionality near the MCID of FMA.…”
Section: Intervention Characteristics and Its Resultsmentioning
confidence: 99%
See 1 more Smart Citation